Application of Anti-SLAPP (Strategic Lawsuit Against Public Participation) Principles in Environmental Case Solutions in Indonesia - Rina Fitri; Muhammad Chairullah; Dian Primadara; Hazimi Abdullah Cut Agam; Bustani (International Journal of Law, Social Science, and Humanities, 2025)
The Anti-SLAPP (Strategic Lawsuit Against Public Participation) principle is one of the important principles in legal protection for environmental activism in Indonesia. This article discusses the application of the Anti-SLAPP principle in resolving criminal cases against environmental activists, with a case study of Decision Number 475/Pid.B/2020/PN Sgl jo. 21/PID/2021/PT BBL. This study uses a normative legal approach with descriptive analysis. The results of the study show that although the Anti-SLAPP principle has been recognized in the Indonesian legal system, its implementation still faces challenges, both in terms of regulations and law enforcement officers. This study recommends the need to strengthen regulations and increase the capacity of law enforcement officers in understanding Anti-SLAPP as part of the principle of protection for environmental advocacy. Keywords: Anti-SLAPP, Environmental Law, Human Rights Defenders, Public Participation, Legal Protection.